Perception of EFL Students on the Use Grammarly Application in Writing Class - Ghaida Nurul Rahma Hakiki (EDUVELOP, 2021)
As EFL students, we cannot separate from writing assignments and articles in English. For some students, it is not easy to express thoughts with good grammar directly. They often require several repetitions of works to avoid making mistakes. Even so, they still make a mistake in grammar. Grammatical errors in the writing class often make it difficult for lecturers to understand student writing content so that students get unsatisfactory feedback. One solution to this problem is implementing the Grammarly application in writing assignments and articles. This study aims to determine students' views on using the Grammarly application in writing assignments and articles. This study uses a qualitative approach with descriptive analysis methods. The research subjects were students of the fifth semester of English Language Education, FKIP Tidar University. The research data used an automatic grammar checker in the learning process of writing namely Grammarly.